Jesuit contribution to science : a history - Udías, Agustín (S.I.) 1935- (Cham, Switzerland Springer, 2015)
This book presents a comprehensive history of the many contributions the Jesuits made to science from their founding to the present. It also links the Jesuits dedication to science with their specific spirituality which tries to find God in all things. The book begins with Christopher Clavius, professor of mathematics in the Roman College between 1567 and 1595, the initiator of this tradition. It covers Jesuits scientific contributions in mathematics, astronomy, physics and cartography up until the suppression of the order by the Pope in 1773. Next, the book details the scientific work the Jesuits pursued after their restoration in 1814. It examines the establishment of a network of observatories throughout the world; details contributions made to the study of tropical hurricanes, earthquakes and terrestrial magnetism and examines such important figures as Angelo Secchi, Stephen J. Perry, James B. Macelwane and Pierre Teilhard de Chardin. From their founding to the present, Jesuits have trodden an uncommon path to the frontiers where the Christian message is not yet known. Jesuits{u2019} work in science is also an interesting chapter in the general problem of the relation between science and religion. This book provides readers with a complete portrait of the Jesuit scientific tradition. Its engaging story will appeal to those with an interest in the history of science, the history of the relations between science and religion and the history of Jesuits
Chapter 1: Clavius and Mathematics in the Collegio Romano -- Chapter 2: Mathematics, Astronomy and Physics in Colleges and Observatories -- Chapter 3: Kircher and Boscovich -- Chapter 4: Jesuit Astronomers in China and India -- Chapter 5: Naturalists, Geographers and Explorers -- Chapter 6: The New Observatories -- Chapter 7: Meteorology. Tropical Hurricanes -- Chapter 8: Earthquakes and Seismology -- Chapter 9: Four Great Modern Scientists -- Chapter 10: Science in Colleges and Universities -- Chapter 11: Epilogue: Jesuit Scientific Tradition -- Appendices. Notes -- Bibliography -- Index of Names
Keywords: Jesuitas; Ciencia